UJI EFEK ANTIRHEUMATOID ARTRITIS EKSTRAK n-BUTANOL DAUN PETAI CINA (Leucaena leucocephala (Lam.) de Wit) PADA TIKUS JANTAN YANG DIINDUKSI COMPLETE FREUND`S ADJUVANT - Amirah, Sitti; Rahman, Safriani; Hi Amin, Rahmatia S (Jurnal Ilmiah As-Syifaa, 2021)
Rheumatoid arthritis is an autoimmune disease characterized by chronic inflammation. The research animed to determine the effect of n-butanol extract of Leucaena leucocephala leaves and the effective dose as antirheumatoid arthritis. It used 15 male rats divided into 5 groups: group I (negative control) was given Na-CMC; group II (positive control) was given a suspension of Methylprednisolone; group III, IV dan V were give the extraxt with doses of 83,3 mg/kgBW, 166,6 mg/kgBW and 333,2 mg/kgBW. The treatment was started by inducing Complete Freund`s Adjuvant intraplantary of 0,1 mL and let it remain until day 16. The therapy was conduction for 14 days orally and the foot volume measurements and observation of the arthritis index were performed on day 17 and 31st. The data analyzed using One Way Anova showed the differences among the groups (p 0,05) and continued with LSD test. The measurement of arthritis index using Kruskal-Wallis showed the differences between groups (p 0,05) proceeded to Mann-Whitney test. In conclusion, the n-butanol extract of Leucaena leucocephalaÂ  leaves had the effect as antirheumatoid